'Scared of going to the clinic': Contextualising healthcare access for men who have sex with men, female sex workers and people who use drugs in two South African cities - Zoe Duby; Busisiwe Nkosi; Andrew Scheibe; Ben Brown; Linda-Gail Bekker (AOSIS, 2018)
Background: Men who have sex with men (MSM), sex workers (SW) and people who use drugs (PWUD) are at increased risk for HIV because of multiple socio-structural barriers and do not have adequate access to appropriate HIV prevention, diagnosis and treatment services. Objective: To examine the context of access to healthcare experienced by these three 'Key Populations', we conducted a qualitative study in two South African cities: Bloemfontein in the Free State province and Mafikeng in the North West province. Method: We carried out in-depth interviews to explore healthcare workers' perceptions, beliefs and attitudes towards Key Populations. Focus group discussions were also conducted with members of Key Populations exploring their experiences of accessing healthcare. Results: Healthcare workers described their own attitudes towards Key Populations and demonstrated a lack of relevant knowledge, skills and training to manage the particular health needs and vulnerabilities facing Key Populations. Female SW, MSM and PWUD described their experiences of stigmatisation, and of being made to feel guilt, shame and a loss of dignity as a result of the discrimination by healthcare providers and other community. members. Our findings suggest that the uptake and effectiveness of health services amongst Key Populations in South Africa is limited by internalised stigma, reluctance to seek care, unwillingness to disclose risk behaviours to healthcare workers, combined with a lack of knowledge and understanding on the part of the broader community members, including healthcare workers. Conclusion: This research highlights the need to address the broader healthcare provision environment, improving alignment of policies and programming in order to strengthen provision of effective health services that people from Key Populations will be able to access.